Utilization of sediments collected from mine tailings for construction materials and industrial use - Villanueva, Seraphim Rafael I.; Candelaria, Ma. Doreen; Samaniego, Jessie O.; Rivera, Alexis Bryan G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Numerous Small-scale Gold mining Facilities in the Philippines produce tailings, which contaminate neighboring water bodies due to the high amounts of heavy metals used in the process of extraction of gold. In this project, these tailings, collected from sedimentation, are used as replacement for fine aggregates in concrete. 0%-50% replacements of fine aggregates, with regards to the total weight used in the concrete, with mine tailings and the corresponding compressive strengths of these mixtures through the mortar experiment are tested. Further experimentation on the behavior of these mortars is done through concrete cylinder testing. Leaching properties, water contamination, and x-ray diffraction tests were also conducted to determine the immobilization of the heavy metals in the concrete. We were able to conclude that a decrease in the compressive strength of the mortar occurs as the percentage of the tailings increase. However, for normal use of mortar requirement for compressive strength, all of the percentage replacements pass the required strength. It is recommended that up to 30% replacement is used in fine aggregates.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Tailings (Metallurgy); Concrete -- Additives